Biosensing and geography: A mixed methods approach. (October 2017) - Osborne, Tess; Jones, Phil Ian
Abstract: Biosensing measures of physiological (somatic) response offer a potentially powerful tool for capturing people's subconscious reactions to environmental stimuli. Combining biosensing with other techniques allows insights to be generated not only about the intensity of somatic response but also, crucially, the underlying causes of that response. Despite pioneering work in this area, a rigorous, empirically-led analysis of biosensing measures in mixed methods research has hitherto been lacking. We address this lacuna through a case study of urban walking, comparing a field-based study (30 participants) with a virtual exercise undertaken in a lab (25 participants). Combining biosensing with data on environmental stimuli (recorded using video/GPS) and interviews, three analytical modes are examined: biosensing-led; environment-led; and thematic-led. The analysis shows how each dataset can add contextualizing information to significant phenomena observed in the others. We demonstrate, however, that biosensing measures become considerably more difficult to interpret beyond the controlled environment of the lab. The paper concludes that biosensing should be seen as a valuable measure in field studies, but one which requires careful interpretation through other datasets, being of limited usefulness and reliability taken alone. Highlights: A rigorous empirically-led analysis is undertaken of mixed methods approaches that utilize biosensing techniques. Biosensors are less reliable in field settings compared to the lab. Mixed methods approaches allow the context for participants physiological (somatic) response to an environment to be analysed. New insights are generated into how cultural geographers and others can research questions of embodiment.